2014
DOI: 10.1513/annalsats.201402-084oc
|View full text |Cite
|
Sign up to set email alerts
|

Natural Progression of Childhood Asthma Symptoms and Strong Influence of Sex and Puberty

Abstract: Rationale: Asthma prevalence, onset, remission and relapse, and healthcare use have been intensively studied. However, asthma symptom progression through childhood and adolescence has not been well studied, in part due to the challenges in obtaining consistent and robust long-term follow-up data on a large series of subjects with asthma.Objectives: To use the asthma diary symptom data of the Childhood Asthma Management Program placebo group (5 yr, 418 subjects, and total 564,518 records) to establish sex-speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
65
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 47 publications
2
65
0
2
Order By: Relevance
“…Asthma prevalence increases in females at the time of puberty, and epidemiological studies have associated puberty, measured by increasing Tanner stages, with decreased asthma symptoms in boys and increased asthma symptoms in girls (Fu et al, 2014). Several studies in women showed changes in hormone levels, either during the menstrual cycle or in taking oral contraceptives, modulated asthma symptoms (Fuseini and Newcomb, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Asthma prevalence increases in females at the time of puberty, and epidemiological studies have associated puberty, measured by increasing Tanner stages, with decreased asthma symptoms in boys and increased asthma symptoms in girls (Fu et al, 2014). Several studies in women showed changes in hormone levels, either during the menstrual cycle or in taking oral contraceptives, modulated asthma symptoms (Fuseini and Newcomb, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…As children age, the switch in asthma prevalence from highest in males to highest in females coincided with the age of puberty onset (5, 14). The Childhood Asthma Management Program (CAMP) study longitudinally tracked the average asthma symptom score as well as progression through puberty, using the Tanner stage metric, in boys and girls ages 4–17 (15•). At approximately age 10, when the Tanner scores start increasing in girls, the average asthma symptom score also increased in girls and declined in boys (15•).…”
Section: Asthma Prevalence Changes During Pubertymentioning
confidence: 99%
“…The Childhood Asthma Management Program (CAMP) study longitudinally tracked the average asthma symptom score as well as progression through puberty, using the Tanner stage metric, in boys and girls ages 4–17 (15•). At approximately age 10, when the Tanner scores start increasing in girls, the average asthma symptom score also increased in girls and declined in boys (15•). Further, asthma symptoms continued to increase in girls as Tanner stages increased (15•).…”
Section: Asthma Prevalence Changes During Pubertymentioning
confidence: 99%
“…The age of this gender switch has not been precisely determined, with conflicting research on whether pubertal stages or puberty are associated with the switch in prevalence [1, 4, 5]. These differences appear to stem from biological differences between sexes as well as sociocultural and environmental differences.…”
Section: Introductionmentioning
confidence: 99%